Transmission loss prediction of silencers by using combined boundary element method and point collocation approach. (December 2015) - Yang, L.; Ji, Z.L.; Wu, T.W.
Abstract: A technique that combines the boundary element method (BEM) and the point collocation approach is proposed to calculate the transmission loss (TL) of silencers in the absence of mean flow and temperature gradient. A long silencer is first divided into several substructures for analysis purposes. The point collocation approach is applied to produce the impedance matrices of any long substructure that has an axially uniform cross section to produce its impedance matrix. On the other hand, the direct mixed-body BEM is used to produce the impedance matrices of any irregular sections. The point collocation approach employs a modal expansion of the cross-sectional modes extracted by the 2D finite element method (FEM), and then matches the sound pressures and particle velocities at the collocation points on both ends to calculate the impedance matrix. All the substructure impedance matrices are then combined to form the resultant impedance matrix of the whole silencer for TL computation. Several test cases are presented to valid the combined technique and to demonstrate its computational efficiency.